Uji Kinerja Emiter Cincin - - Reskiana; Budi Indra Setiawan; Satyanto K. Saptomo; Popi Redjekiningrum Dwi Mustatiningsih (Jurnal Irigasi, 2014)
Water scarcity causes the utilization of dryland is not maximal in supporting agricultural production in Indonesia. Efficient irrigation technology which is economically affordable by farmers needs to develop. This research aimed to provide an irrigation ring typed emitter that can be placed under the soil surface. In this research, porous materials made of textiles were tested for its permeability that matches the permeability of the soil. We got 5 textiles made of Legacy having permeability of 1.54 cm h-1, Colosal 0.76 cm h-1, Veronica 8.16 cm h-1, Kyramat 5.28 cmh-1, and Parasut 0.06 cmh-1. This selected textile was rolled covering a ring typed perforated water hos (ring emitter). These emitters were then tested to irrigate potted water melon plants in a greenhouse. The results show ring emitters covered with Legacy and Colossal have better water productivity, 0.64 kg m-3 and 1.90 kg m-3, respectively with the averaged water discharge 0.52 l h-1 and 1.08 l h-1.